2018 Korean Society of Hypertension guidelines for the management of hypertension: part I-epidemiology of hypertension - Hyeon Chang Kim; Sang-Hyun Ihm; Gheun-Ho Kim; Ju Han Kim; Kwang-il Kim; Hae-Young Lee; Jang Hoon Lee; Jong-Moo Park; Sungha Park; Wook Bum Pyun; Jinho Shin; Shung Chull Chae (BMC, 2019)
Abstract The Korean Society of Hypertension guideline defines hypertension as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg, where the effectiveness of pharmacological treatment has been established. It is confirmed that higher blood pressure levels are associated with increased risk of cardiovascular disease and mortality also in the Korean population. About one third of Korean adults aged 30 years or older are estimated to have hypertension, and the prevalence of hypertension gradually increases as the age increases. The awareness, treatment, and control rates of hypertension are generally improving in Korea, but more efforts are required to increase awareness and treatment among younger patients with hypertension and to improve lifestyle modification compliance at all ages. More studies are required to determine the magnitude and impact of white coat hypertension and masked hypertension in the Korean population.